Assessment of addiction behavior and spermatogenesis in glial cell line-derived neurotrophic factor-treated cannabis-addicted rats: An experimental study - Rozhina Laleh; Mitra Heydari Nasrabadi; Parvin Khodarahmi; Jamshid Soltani (International Journal of Reproductive BioMedicine)
Background: Cannabis addiction poses risks to male fertility by lowering levels of glial cell line-derived neurotrophic factor (GDNF), which is vital for spermatogenesis. Objective: This research aimed to determine if the injection of exogenous GDNF into the brain of cannabis-addicted rats has a positive impact on their behavior and spermatogenesis.